Endriejaviškių pejoratyvinė leksika (neigiamieji žmogaus apibūdinimai) - Jasiūnaitė, Birutė (Kalbotyra, 1995)
On the basis of the semantic analysis of 375 words, used for negative characterizing of man in one of the Western Lithuanian dialects, the following conclusions can be drawn: 1. Though we can find many dialectal words used in a pejorative sense to describe various defects of man’s character and appearance, only a small part of them can be treated as actual swear-words. 2. The number of such negative words in the dialect we deal with is inversely proportional to the quantity of compliments and other means of politeness. 3. The negative characteristics of man in most cases are motivated words (we mean semantic or derivative motivation), so they can be treated as new words. 4. If we deal with the dialectal vocabulary we cannot pay any attention to such sources of supplementary information as ethnography, folklore and other trends of culture. First of all we must study the linguistic part of the problem.